Quality of sleep after COVID-19 infection: a cross-sectional study in the Southern Italy - Sansone, Vincenza; Angelillo, Silvia; Paduano, Giovanna; Pileggi, Claudia; Nobile, Carmelo Giuseppe Angelo; Di Giuseppe, Gabriella (Frontiers in Psychiatry, 2024)
Introduction This study investigated the quality of sleep in a sample of individuals from Southern Italy after the major waves of the COVID-19 pandemic, with the aim of evaluating how sleep patterns changed. Methods A cross-sectional study was conducted between March 2022 and January 2023 and involved adults who had a COVID-19 infection, who were invited to complete a self-administered online questionnaire. Results A total of 408 individuals participated in the survey. Overall, 66.4% had a reduction in social relations; 72.1% had an increase in the use of social media; and 86%, 77.2%, and 71.1% reported an extremely severe level of anxiety, stress, and depression, respectively. Almost all of the respondents had a Pittsburgh Sleep Quality Index score (PSQI) ≥5, indicating poor sleep quality. Subjects with a severe or extremely severe depression score, a severe or extremely severe stress score, who had a job, and who had someone close who died because of a COVID-19 infection were more likely to have a high PSQI global score. The use of sleep medication in the past months was significantly higher in those who were older, who had a job, who had a COVID-19 infection in the first and second waves, who had someone close who died from COVID-19, and who did not have changes in social relationships during the pandemic. Moreover, participants with severe or extremely severe depression scores, with severe or extremely severe stress scores, who were women, and who were older had troubles staying awake while engaging in social activities during the past month. Conclusion The results bring to light the high prevalence of poor sleep quality among individuals who were infected with SARS-CoV-2. Future research is needed to understand whether these disturbances are still present in the endemic period and whether it is necessary to investigate further determinants that have affected and/or are affecting sleep quality.